Is international junior success a reliable predictor for international senior success in elite combat sports?. Issue 4 (21st April 2018) - Li, Pingwei; De Bosscher, Veerle; Pion, Johan; Weissensteiner, Juanita R.; Vertonghen, Jikkemien
Abstract: Currently in the literature, there is a dearth of empirical research that confirms whether international junior success is a reliable predictor for future international senior success. Despite the uncertainty of the junior–senior relationship, federations and coaches still tend to use junior success as a predictor for long-term senior success. A range of former investigations utilising a retrospective lens has merely focused on success that athletes attained at junior level competitions. Success that was achieved at senior-level competitions but at a junior age was relatively ignored. This study explored to what extent international senior success can be predicted based on success that athletes achieved in either international junior level competitions (i.e. junior medalists ) or senior competitions at a junior age (i.e. early achievers ). The sample contains 4011 international male and female athletes from three combat sports (taekwondo, wrestling and boxing), who were born between 1974 and 1990 and participated in both international junior and senior-level competitions between 1990 and 2016. Gender and sport differences were compared. The results revealed that 61.4% of the junior medalists and 90.4% of the early achievers went on to win international medals at a senior age. Among the early achievers, 92.2% of the taekwondo athletes, 68.4% of the wrestling athletes and 37.9% of the boxing athletes could be reliably "predicted" to win international senior medals. The findings demonstrate that specific to the three combat sports examined, international junior success appears to be an important predictor to long-term international senior success.